Good fences make good neighbours : a qualitative, interpretive study of human–baboon and human–human conflict on the Cape Peninsula - Terblanche, Renelle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.